2019
DOI: 10.3126/jnps.v38i2.20547
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hand Hygiene Knowledge among Residents and Nursing staffs at Nobel Medical College Teaching Hospital, Biratnagar

Abstract: Introduction: Hand hygiene is a very simple and cost-effective procedure to prevent cross-transmission of microorganisms. The compliance of residents and nursing staffs with hand hygiene guidelines seems to be vital in preventing disease transmission among patients. The objective of the study was to assess the knowledge of residents and nursing staffs with regard to hand hygiene. Material and Methods: This was an institution based descriptive cross-sectional study conducted among 55 respondents (29 nursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
4
2
2
Order By: Relevance
“…Our findings were inconsistent with other study in Nepal carried out by Yadav SK, et al that found only 9% of participants had good knowledge on hand hygiene, which proved that their health care workers had moderate knowledge on hand hygiene [24]. Another study in Vietnam carried out by Cam Dung, et al found that health care workers had good knowledge of hand hygiene [28].…”
Section: Ethical Approvalcontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings were inconsistent with other study in Nepal carried out by Yadav SK, et al that found only 9% of participants had good knowledge on hand hygiene, which proved that their health care workers had moderate knowledge on hand hygiene [24]. Another study in Vietnam carried out by Cam Dung, et al found that health care workers had good knowledge of hand hygiene [28].…”
Section: Ethical Approvalcontrasting
confidence: 99%
“…A study in Jeddah, Saudi Arabia, found that most health care workers used alcohol and handwashing with water before touching the patient and handwashing with water more than alcohol after touching the patient [5]. Additionally, it differed from another study in Nepal carried out by Yadav SK, et al that found that health care workers mostly used alcohol-based hand rubs [24]. It differed from another study in Al-Qassim, Saudi Arabia, that found soap and water were the most common agents for cleansing the hands of HCWs [18].…”
Section: Associated Factors With Level Of Knowledge and Attitude Of Hand Hygienementioning
confidence: 87%
“…Data collection in this study was before COVID-19 pandemic, and despite that the transmission of SARS-CoV-2 through air circulation is possible, it is not the main route of transmission. We found only (19.0%) of nurses were aware that the most frequent source of germs responsible for healthcare associated infections is present on or within the patient, which is low compared to a study in Biratnagar, in Nepal (30.0%) [28].…”
Section: Discussioncontrasting
confidence: 77%
“…Hand hygiene is an effective way to prevent HAIs and reduce length of stay, morbidity, mortality and healthcare cost (Doronina et al ; World Health Organization ; Yadav & Giri ); however, compliance with proper hand hygiene practice is low among healthcare providers in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Hand hygiene is the most cost‐effective means to control HAIs and nurses play a key role as they are the front‐line healthcare workers with the most patient contact (Doronina et al ; Yadav & Giri ). Nurses’ compliance with hand hygiene guidelines seems to be critical to reduce HAIs (Vermeil et al ).…”
Section: Introductionmentioning
confidence: 99%